Inclusive education beyond formal settings: AR and VR as accessibility strategies for deaf and hard-of-hearing individuals - González-Afonso, Miriam Catalina; Perdomo-López, Carmen de los Ángeles; Plasencia-Carballo, Zeus; Pérez-Jorge, David (Frontiers in Education, 2026)
This scoping review synthesizes the evidence on how augmented reality (AR) and virtual reality (VR) enhance accessibility and participation for deaf and hard-of-hearing individuals in non-formal educational settings (e.g., museums, libraries, heritage sites and community programs). Following the PCC and PRISMA-ScR frameworks, studies published between 2015 and 2025 in English, Spanish, Portuguese or French were searched in Scopus, Web of Science and PubMed. After peer screening, 9 manuscripts were analysed (from 246 unique records; 27 full texts reviewed). The most frequent contexts included libraries (orientation and anxiety reduction), cultural experiences with immersive subtitling, technical training using AR and sign language, and autonomous/community-based learning. Visual accessibility features predominated (subtitles, sign language support, 3D visualizations), with generally positive but exploratory evidence (small samples, short-term studies). We conclude that AR/VR have clear potential, but more robust designs, standardization (e.g., subtitles/avatars), co-design with deaf communities and evaluations of sustainability and scalability are needed.